ANALYSIS CONTROL SUPPLIES RAW MATERIALS TO EFFICIENCY COST, USING THE METHOD OF ECONOMIC QUANTITY ORDER AT CV. PQR - Wartoyo Hadi (STIE Binaniaga, 2016)
The purpose of the implementation of this research is to find the effectiveness of supplies raw materials, the method of analysis data used in the square is the smallest trend for planning raw materials and controling supplies use method of economic order quantity (EOQ) analyze reorder point. Analysis reorder point and safety stock. And analyzes efficiency cost of raw materials. Forecasting raw materials years 20x7 according to the smallest trend, cloth and dakron happened the difference is greater than of the target needed (according to a company); controling supplies raw materials with the methods eoq in 20x7 more effective than reservations raw materials cloth and dakron and more efficient than cost raw materials. The company should review the policy of forecasting raw material supplies that had been undertaken and make planning supplies the raw material that more accurate using the firm’s historical data and not only targeting the output production next year, so that machines production can be optimized. Considering the use of control supplies with the methods economic order quantity to companies, so this analysis can determine material reservations, supplies safety, maximum supplies to avoid the risk of running out of raw materials, because the companies often happened less dressed up a result of reservations that time is inaccurate, the lack of safety stock and the deferred the delivery of goods which often disturb the production process, by this method can prevent these things, so that the production process can run smoothly and minimize the cost of raw materials supplies.Keywords: control, efficiency and cost of raw materials.